2022
DOI: 10.2147/vmrr.s370733
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness, Prevalence and Potential Determinants of Bovine Tuberculosis in Selected Districts of Gamo Zone, Southern Ethiopia

Abstract: Purpose Bovine tuberculosis (bTB) is infectious chronic disease of animals mainly caused by bacillus Mycobacterium bovis. It is known endemic disease of cattle in Ethiopia. In the current study sites, there is little information on bovine tuberculosis. Thus, this study was aimed to assess public awareness; and estimate prevalence and potential a risk factors of bovine tuberculosis. Methods A cross-sectional study was conducted, November 2018 to May 2019, on dairy cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Seventeen African and two Asian studies investigated farmers’ awareness that bTB is a zoonosis. Only 12 of these studies explored this zoonotic awareness after asking farmers whether they knew bTB existed (33–35, 38, 40, 42, 46, 48, 62, 65). Of these 12 studies, four reported awareness that bTB is a zoonosis as the proportion of farmers that said ‘yes’ to this question among those who previously confirmed awareness that bTB exists (33, 34, 42, 48) (blue lines, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen African and two Asian studies investigated farmers’ awareness that bTB is a zoonosis. Only 12 of these studies explored this zoonotic awareness after asking farmers whether they knew bTB existed (33–35, 38, 40, 42, 46, 48, 62, 65). Of these 12 studies, four reported awareness that bTB is a zoonosis as the proportion of farmers that said ‘yes’ to this question among those who previously confirmed awareness that bTB exists (33, 34, 42, 48) (blue lines, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies investigated whether farmers knew that raw milk and dairy (Africa n=8; Asia n=2) or raw meat (Africa n=6) consumption could result in zoonotic infection with bTB (28, 30, 31, 33, 44, 62). Except for the farmer populations investigated by Kazoora et al (44), most studies found this knowledge was prevalent among less than 30% of the farmers interviewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 1953 and 1980, this program was successful in many European Union member states as well as seven countries in central Europe ( Jemal, 2016 ). It is necessary to provide specific hygiene standards for foods of animal origin to stop diseased animals from getting into the food chain and lower the hazards connected with consuming tainted milk and meat ( Tora et al ., 2022 ). Systems for inspecting meat need to be improved and intended to stop the general population from consuming tainted goods.…”
Section: Introductionmentioning
confidence: 99%